Diagnosis and Management of Nonalcoholic Fatty Liver Disease and Its Hemostatic/Thrombotic and Vascular Complications - Targher, Giovanni; Byrne, Christopher D. (Seminars in Thrombosis and Hemostasis, 2013)
Nonalcoholic fatty liver disease (NAFLD) represents a spectrum of progressive liver disease encompassing simple steatosis, nonalcoholic steatohepatitis (NASH), fibrosis, and, ultimately, cirrhosis. NAFLD is strongly associated with features of the metabolic syndrome including abdominal overweight/obesity, hypertension, atherogenic dyslipidemia, glucose intolerance, or type 2 diabetes. With the advent of increasingly sedentary lifestyles and changing dietary patterns, the prevalence of obesity and insulin resistance has increased and, with this, NAFLD has rapidly become the most common cause of chronic liver disease in many developed countries. Importantly, accumulating evidence indicates that NAFLD is strongly associated with a prothrombotic tendency, which may, at least in part, contribute to the increased risk of atherothrombotic events observed in these patients. NAFLD, especially in its necroinflammatory form (NASH), releases a variety of proinflammatory and prothrombotic mediators that play important roles in the development and progression of acute atherothrombotic complications. NAFLD also exacerbates systemic and hepatic insulin resistance and causes atherogenic dyslipidemia. The purpose of this review is to briefly discuss the epidemiology and diagnosis of NAFLD, to summarize the rapidly expanding body of evidence that supports a strong association between NAFLD and various disorders of coagulation and fibrinolysis and their implications for the development of atherothrombotic complications, and to discuss some of the treatment options that may influence both NAFLD and its related vascular complications.
Keywords: nonalcoholic fatty liver disease; atherothrombosis; blood coagulation disorders; hemostatic factors; inflammation